Digital Marketing Assistance on Used Car Buying and Selling Community in Makassar City - Hasnidar; Jusri; Achmad Ridha; Azlan Azhari (www.amertainstitute.com, 2025)
The rapid growth of the used car trading sector in Makassar City has not been matched by sufficient digital marketing competencies among its business actors. This community service activity aims to strengthen the digital capacity of the Turbo Car Community through structured training and mentoring in social media-based marketing strategies. Conducted over two days in Malino City, the program included digital marketing workshops and hands-on practice in utilizing Facebook Marketplace and Instagram. A preliminary survey was undertaken to assess participants’ initial digital literacy and identify promotional barriers. The training sessions introduced participants to key concepts of digital marketing, digital consumer behavior, and content strategy, followed by guided mentoring to create and manage online promotional content. Direct assistance was provided to six selected showrooms in optimizing their online presence. The results demonstrated a marked improvement in participants’ understanding, confidence, and ability to independently implement digital marketing strategies. Furthermore, the use of digital platforms proved effective in expanding market reach, increasing sales potential, and enhancing customer engagement. This initiative represents a strategic step in accelerating digital transformation among micro and small enterprises (MSEs) in the automotive sector and can serve as a replicable model for similar business communities across Indonesia. The long-term expectation is to foster continuous innovation and sustainability in digital marketing practices within local economies.